Diseño y elaboración de un software educativo para mejorar el proceso de enseñanza - aprendizaje de la asignatura de ciencias naturales bloques 1, 2 y 3 del décimo año de educación general básica del colegio de bachillerato fiscal “Riobamba” - sección nocturna, de la ciudad de Riobamba, periodo lectivo 2013-2014 - Díaz Encalada, Sonia Jackeline (2014)
This thesis entitled: DESIGN AND DEVELOPMENT OF AN EDUCATIONAL SOFTWARE TO IMPROVE THE 1, 2 AND 3 BLOCK NATURAL SCIENCE SUBJECT TEACHING - LEARNING PROCESS OF BASIC GENERAL EDUCATION TENTH YEAR "RIOBAMBA" HIGH SCHOOL - NIGHT, SECTION RIOBAMBA CITY, PERIOD 2013-2014. The overall objective is referred to design and develop an educational software to improve the 1, 2 and 3 block Natural Science Subject Teaching - Learning Process of Basic General Education Tenth Year "Riobamba" high school Night Section Riobamba city, period 2013-2014. The methods used to accomplish the objectives were scientific, deductive -inductive, descriptive and quantitative, which helped me to make the general analysis and diagnosis of the problem; techniques and instruments used were the same survey that was administered to students in the tenth year of basic general education and applied to interview teachers. The expected results are in line with this objective, since, from students’ surveys indicated that 95% don’t have a technological support tool for the subject of Natural Sciences, 98% of students said that have an educational software for the subject of Natural Sciences would be fabulous and significantly INFORMÁTICA EDUCATIVA improve their academic performance, while 82% said that classes today are a bit boring, because as teaching materials and primary source of information is only used Text Book issued by the Ministry of Education, also 70% say that the blocks of greater complexity in the course are 1,2 and 3, the elements that must have educational software, was also obtained for which the students indicated the following: 53% images, animations and text 96%, 11% audio, activities, videos and evaluations 9%; referring to the interviews applied to teaching the following results were achieved: that to teach the subject of Natural Sciences solely rely on the Text Book, likewise, express an Educational Software help much and help the student to grasp and strengthen more complex issues, and that the application should be easy to manage, contain major and relevant ideas, and especially motivating students also indicated some of the most complex issues of 1, 2 and 3 block.